Peran LSM Dalam Resolusi Konflik Tapal Batas Antara Nagari Sumpur Dengan Nagari Bungo Tanjuang, Kabupaten Tanah Datar - Sri Rahmadani (LPPM Universitas PGRI Sumatera Barat, 2015)
The Third parties in the resolution of conflictwas expected to change the behavior of the parties in conflict, even pushed the parties toward an agreement to end the conflict. NGO as the third party is seen independent and can be fair in the resolution of conflict, can do some attempts to encourage the parties in conflict toward an agreement.One example of conflict involving NGO in an effort to resolve the boundary conflicts between Nagari Sumpur and Nagari Bungo Tanjuang, regency of Tanah Datar. Assignment NGO as mediator in resolution of conflict after several attempts taken by the government. This article explained the various efforts and achievement has done by NGO as mediator resolution of conflict both nagari until the formation of representative group become key success in mediation. In addition in this article is also explained the reason NGO that has not been able to achieve an aggrement in resolution of conflict both nagari.Pihak ketiga dalam resolusi konflik diharapkan dapat merubah perilaku para pihak yang berkonflik, bahkan mendorong para pihak menuju kesepakatan untuk mengakhiri konflik. LSM sebagai pihak ketiga dipandang independen dan dapat bersikap adil dalam resolusi konflik, dapat melakukan beberapa upaya untuk mendorong pihak yang berkonflik menuju kesepakatan. Salah satu contoh konflik yang melibatkan LSM dalam penyelesaiannya adalah konflik tapal batas antara Nagari Sumpur dengan Nagari Bungo Tanjuang, Kabupaten Tanah Datar. Penunjukan LSM sebagai mediator dalam penyelesaian konflik setelah beberapa upaya yang ditempuh oleh beberapa pihak dari pemerintahan. Tulisan ini memaparkan berbagai upaya dan pencapaian yang telah dilakukan LSM sebagai mediator penyelesaian konflik kedua nagari hingga terbentuknya perwakilan kelompok yang menjadi kunci keberhasilan dalam mediasi. Selain itu dalam tulisan ini juga memaparkan alasan LSM yang belum mampu mencapai kesepakatan dalam penyelesaian konflik kedua nagari.